Unveiling the Potential of YOLOv9 through Comparison with YOLOv8 - Hafedh Mahmoud Zayani (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study introduces YOLOv9, a new object detection model building upon the success of YOLOv8. While YOLOv8 has delivered impressive results, there was a push to further enhance accuracy and efficiency. We delve into the architectures of both YOLO models to understand the trade-off between training speed and accuracy. YOLOv9 introduces additional complexity compared to its predecessor, which translates to superior performance. To evaluate the models' capabilities, we leveraged a tomato disease detection dataset from Roboflow. This dataset encompasses three disease classes for tomato fruits, along with a healthy class. Our experiments demonstrate that YOLOv9 achieves a significant improvement in accuracy (93.6% vs. 92%), while maintaining comparable training efficiency. However, it requires slightly longer training times compared to YOLOv8. To further substantiate these results, we present comprehensive analyses of precision, recall, F1-score, and loss functions during both training and validation stages. Additionally, in the testing phase, YOLOv9 exhibits superior precision in detecting tomato diseases. While requiring slightly more training resources, YOLOv9 offers a compelling trade-off between accuracy and efficiency. This makes it a promising choice for applications where precise object detection is paramount.